The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fphys.2022.965210
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole cotreatment with progestin-primed ovarian stimulation in women with polycystic ovary syndrome undergoing IVF treatment

Abstract: Background: Progestin is an alternative to gonadotropin-releasing hormone (GnRH) analogues in the follicular phase to suppress the premature luteinizing hormone (LH) surge in women with polycystic ovary syndrome (PCOS). However, progestin-primed ovarian stimulation (PPOS) is always accompanied by increased pituitary suppression and gonadotropin consumption. Previous studies suggested that letrozole appeared to have the potential to reduce the total gonadotropin dose required for ovarian stimulation. A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The results suggested that the clinical pregnancy of patients with the Le PPOS protocol was significantly higher than with the traditional PPOS protocol. Those results are supported by a previous study that showed higher implantation rates with Le PPOS compared with PPOS in patients with PCOS 20 . This study is unique in that the PSM method was used; the advantages of Le PPOS can be better reflected when the characteristics of the two groups are similar.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The results suggested that the clinical pregnancy of patients with the Le PPOS protocol was significantly higher than with the traditional PPOS protocol. Those results are supported by a previous study that showed higher implantation rates with Le PPOS compared with PPOS in patients with PCOS 20 . This study is unique in that the PSM method was used; the advantages of Le PPOS can be better reflected when the characteristics of the two groups are similar.…”
Section: Discussionsupporting
confidence: 83%
“…MPA cotreatment starting on MC3 can block the premature LH surge, but this strategy will fail if MPA is started during the mid‐follicular phase, at least in women with multiple follicles and high E2 levels 6 . In the present study, MPA was used from MC6 in the Le PPOS group, and there were no premature LH surges, as previously observed in women with polycystic ovary syndrome (PCOS) 20 . The results suggest that letrozole might create an environment with low estrogen levels and allow a reduced time and dose of MPA.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous research has shown that 10 mg of MPA effectively inhibits spontaneous ovulation, whereas 5 mg does not yield the same results ( 11 ). However, conflicting findings have been reported regarding the appropriate MPA dosage for preventing untimely LH surges, with some studies suggesting that daily doses of 4 mg ( 12 , 13 ) or 6 mg ( 3 , 6 ) are sufficient. In our previous study, we demonstrated that coadministration of letrozole (LE) with MPA during ovarian stimulation for IVF achieved comparable embryo and pregnancy outcomes while reducing the required MPA dosage ( 14 ).…”
Section: Introductionmentioning
confidence: 99%